Website Based Garbage Bank Information System In CV Karya Maju Bersama - Muhamad Masjun Efendi; Satriawan, Manda (Alpatih Harapan Semesta, 2023)
Garbage is residual material produced from a production process, both industrial and household. So, it is necessary to deal with problems that arise from waste, one of which is the existence of a waste bank. The processing of data in the waste bank is still done manually, namely by recording with a book. Therefore, along with the rapid advancement of technology, a web-based system was created that can help the waste transaction process at the waste bank. In the process of making the system, research was carried out at the Asri Raharjo Garbage Bank, Pati District, Pati Regency. This study uses the prototype method as a system development method. While in data collection the author uses the method of observation, interviews, literature studies, The results of the study are in the form of a web-based information system that assists officers in serving transactions and customers checking their savings history independently